2016
DOI: 10.1109/tnsre.2016.2523678
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Varying Networks in P300: A Task-Evoked EEG Study

Abstract: P300 is an important event-related potential that can be elicited by external visual, auditory, and somatosensory stimuli. Various cognition-related brain functions (i.e., attention, intelligence, and working memory) and multiple brain regions (i.e., prefrontal, frontal, and parietal) are reported to be involved in the elicitation of P300. However, these studies do not investigate the instant interactions across the neural cortices from the hierarchy of milliseconds. Importantly, time-varying network analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 58 publications
1
70
0
Order By: Relevance
“…Another point is that we selected only Ge from the four BN properties as a component of fusion feature for emotion recognition. According to the graph theory, Ge represents the information integration and the exchange efficiency of the whole network (Li et al, 2016). The statistical results showed that Ge was more sensitive than other BN properties in depicting the differences among the different emotional states.…”
Section: Superiority Of High Gamma Band Features In Emotion Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another point is that we selected only Ge from the four BN properties as a component of fusion feature for emotion recognition. According to the graph theory, Ge represents the information integration and the exchange efficiency of the whole network (Li et al, 2016). The statistical results showed that Ge was more sensitive than other BN properties in depicting the differences among the different emotional states.…”
Section: Superiority Of High Gamma Band Features In Emotion Recognitionmentioning
confidence: 99%
“…However, the network connections and information processing and propagation in these time windows remain unclear. In the future, we will construct time-varying BNs (Li et al, 2016) and investigate the neural mechanism of the brain in more precise time windows.…”
Section: Superiority Of High Gamma Band Features In Emotion Recognitionmentioning
confidence: 99%
“…The results of statistical tests denote that both cases are significantly distinct with each other in LP (p=0.049) and RP (p=0.007) in terms of their designated R values. Denser bilateral cortical activity is observed over parietal regions in TR case that corresponds to P300 response [105,115-118] and motor coordination for button pressing [76,119,120]. Thus, NTNR case has lower bilateral parietal activity as no P300 and motor responses are required for non-target stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…EEG was pre-processed by averaging, re-referencing and 0.5–30 Hz band-pass filtering prior to the time-varying network analysis. The time-varying network analysis usually requires several segmentations (i.e., trials in evoked EEG experiment) to enable the construction of a reliable network in order to capture the brain architectures and networks (Hu et al, 2012 ; Li et al, 2016 ). In this work, compared to the time-varying network analysis for the evoked EEG that usually has the definite stimulus labels, one drawback here is that no exact events were labeled for the inter-ictal discharging during the 24-h EEG monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we assume that the time-varying network patterns may provide useful information to uncover the abnormal information processing and propagation when inter-ictal discharging is observed. Consequently, the time-varying network analysis (i.e., adaptive directed transfer function) which can be applied to investigate the dynamic network patterns during certain task (Li et al, 2016 ) is vital in establishing the corresponding time-varying networks during inter-ictal discharging. Moreover, given the fact that the inter-ictal spiking activity presented here is similar to ictal activity (Wilke et al, 2011 ) and the inter-ictal spiking yet easier to be obtained than ictal data.…”
Section: Introductionmentioning
confidence: 99%